EFEKTIFITAS PEMBERIAN MADU CLOVER HONEY TERHADAP PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI - Sri Wahyuni; Mustika Pramestiyani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Adolescent girls who experience 30% menstruation have the potential to experience anemia. The purpose of this study was to determine the effectiveness of clover honey on increasing hemoglobin levels of adolescent girls. This type of research is a quasi-experimental with non-randomized control group design. The sampling technique used is purposive sampling. The number of samples was a total of 32 respondents who were divided into 4 groups, with details of the group giving 1 spoon of honey, 8 people, the group giving 2 spoons of honey, 8 people giving the honey 3 spoons, and the control group not giving honey as much as 8 people. person. 1 tablespoon (15 ml) of honey had a significant effect on increasing Hb levels with an increase of 0.87 g/dl. Giving 2 tablespoons (30 ml) of honey had a significant effect on increasing Hb levels with an increase of 1.1 g/dl. 3 tablespoons (45 ml) of honey had a significant effect on increasing Hb levels with an increase of 2.24 g/dl. For the control group, the increase was not significant, with an increase of 0.11. The most effective dose of honey in increasing Hb levels in adolescent girls is honey with a dose of 3 spoons (45 ml).